Reconstruction of Roles and Responsibilities of The Board of Directors in Share Repurchase in Limited Liability Company Based on Fair Values: Liabilty Company - Mashdurohatun, Anis; Ambarita , Lenny Mutiara; Gunarto, (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This research aims to find out the roles and responsibilities of the board of directors in repurchasing shares in limited companies that have not been fair and to reconstruct the roles and responsibilities of the board of directors in repurchasing shares in limited companies based on fair values. This research is a sociolegal research, that is, an alternative approach that tests doctrinal studies of law. The word 'socio' in sociolegal represents the correlation between the context in which the law is located (an interface with a context within which law exists). It was found that the Board of Directors is jointly and severally liable for losses suffered by shareholders in good faith, arising from repurchases that are null and void due to the law. This does not provide fair/balanced legal protection for the parties. The fair values in buying shares are to provide balanced and proportional legal protection. Reconstruction of the roles and responsibilities of the Board of Directors in the repurchase of shares in a limited company based on fair values by carrying out reconstruction of Article 37 paragraph (3) and (5) of Law Number 40 Year 2007 concerning Limited Liability Companies.